2015
DOI: 10.4088/jcp.14m09029
|View full text |Cite
|
Sign up to set email alerts
|

MDDScore

Abstract: Background: Previously, a biomarker panel was developed for use as an aid to major depressive disorder (MDD) diagnosis; it consisted of 9 biomarkers associated with the neurotrophic, metabolic, inflammatory, and hypothalamicpituitary-adrenal axis pathways. This panel and associated algorithm produced good clinical sensitivity and specificity (92% and 81%, respectively) in differentiating MDD patients from individuals without MDD. To further validate the panel, we performed a prospective study using a larger se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 61 publications
1
13
2
Order By: Relevance
“…This resulted in a poor performance (AUC = 0.55) for detecting NESDA depression patients and a moderate performance for detecting first-/recent-onset unmedicated patients from specialised mental healthcare (AUC = 0.75; stage 1 cohorts). Recently, Bilello et al [28] published a further study reporting on refinement of the MDDScore algorithm using samples from 68 depression patients and 86 controls with a test sensitivity and specificity >90%. Unfortunately, we were not able to reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in a poor performance (AUC = 0.55) for detecting NESDA depression patients and a moderate performance for detecting first-/recent-onset unmedicated patients from specialised mental healthcare (AUC = 0.75; stage 1 cohorts). Recently, Bilello et al [28] published a further study reporting on refinement of the MDDScore algorithm using samples from 68 depression patients and 86 controls with a test sensitivity and specificity >90%. Unfortunately, we were not able to reproduce these findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Papakostas et al [25] and subsequently Bilello et al [28] reported on development and refinement of a 9-analyte panel (MDDScore test) to discriminate severe recurrent depression patients from controls with a test specificity and sensitivity >90%. However, it has not been tested on naturalistic patient and control populations recruited from the general population and primary healthcare settings, where the need is greatest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to achieving high sensitivity and specificity in their pilot study, Papakostas et al also produced a similar performance in their replication study. This group further refined their model algorithm by factoring in gender, BMI, and normalized cortisol levels ( 219 ). Another group used CSF concentrations of multiple analytes including inflammatory biomarkers (IL-6), serotonin metabolites (5-hydroxyindoleacetic acid), dopamine metabolites (homovanillic acid), and HPA axis biomarkers (hypocretin) to detect severe suicidal behavior and increased risk of completing suicidal attempts in MDD patients ( 220 ).…”
Section: Proteomics Metabolomics and The Utility Of Multiplex Assaymentioning
confidence: 99%
“…However, late studies showed that a single protein has a little diagnostic value among diverse populations because the results are not always consistent. Recently, studies found that combined different serum proteins would provide a much higher diagnostic value than a single protein 17 20 , which indicated that this kind of combination could potentially become a diagnostic tool.…”
Section: Introductionmentioning
confidence: 99%